Daman and Diu Draft Annual Plan 1994-95 - Planning Commission (Planning Commission, 1994)
The Planning Commission vide letter No PC(P)2/2/93- Guidelines dated 7th September'93 has, inter-alia, indicated that priorities for Annual Plan 1994-95 should reflect the thrust areas of the Eighth Plan and be broadly on the same lines as of Annual Plan 1993-94. Thus, employment generation, containment of population growth, diversification of Agriculture, strengthening of infrastructural facilities etc. should receive necessary priority. Adequate funds should also be provided for the ongoing projects before proposing any new scheme for inclusion.
Union Territory of Daman and Diu, Department of Planning and Statistics